Bioethanol as a Renewable Energy Solution: Opportunities and Challenges in Agricultural Waste Utilization - Perdana, Rini (CV. Science Tech Group, 2024)
In the face of climate change challenges and declining fossil energy resources, bioethanol is emerging as an environmentally friendly renewable energy solution. This article aims to review the potential, opportunities, and challenges in utilizing agricultural waste as the main raw material for bioethanol production. By analyzing various recent studies, it is found that agricultural wastes such as rice straw, corn cob, and bagasse have significant carbohydrate content for conversion into ethanol. Second-generation bioethanol production technologies utilizing lignocellulose offer higher efficiency than previous generations but face technical and economic challenges, including complex pretreatment requirements and high production costs. This review shows that bioethanol utilization can reduce dependence on fossil fuels while providing a sustainable solution for waste management. Policy support, technological innovation, and cross-sector collaboration are needed to accelerate the development of agricultural waste-based bioethanol, especially in developing countries such as Indonesia.